Childhood body size directly increases type 1 diabetes risk based on a lifecourse Mendelian randomization approach - Richardson, Tom G.; Crouch, Daniel J. M.; Power, Grace M.; Morales-Berstein, Fernanda; Hazelwood, Emma; Fang, Si; Cho, Yoonsu; Inshaw, Jamie R. J.; Robertson, Catherine C.; Sidore, Carlo; Cucca, Francesco; Rich, Steven S.; et al. (Nature communications, 2022)
The rising prevalence of childhood obesity has been postulated as an explanation for the increasing rate of individuals diagnosed with type 1 diabetes (T1D). In this study, we use Mendelian randomization (MR) to provide evidence that childhood body size has an effect on T1D risk (OR = 2.05 per change in body size category, 95% CI = 1.20 to 3.50, P = 0.008), which remains after accounting for body size at birth and during adulthood using multivariable MR (OR = 2.32, 95% CI = 1.21 to 4.42, P = 0.013). We validate this direct effect of childhood body size using data from a large-scale T1D meta-analysis based on n = 15,573 cases and n = 158,408 controls (OR = 1.94, 95% CI = 1.21 to 3.12, P = 0.006). We also provide evidence that childhood body size influences risk of asthma, eczema and hypothyroidism, although multivariable MR suggested that these effects are mediated by body size in later life. Our findings support a causal role for higher childhood body size on risk of being diagnosed with T1D, whereas its influence on the other immune-associated diseases is likely explained by a long-term effect of remaining overweight for many years over the lifecourse. The rise in type 1 diabetes is thought to be related to increased childhood obesity, but this relationship is not well understood. In this study, the authors utilize Mendelian randomization to separate the direct and indirect effects of childhood body size on risk of type 1 diabetes and 7 other immune-associated disease outcomes.